As problemáticas do regime da inversão do contencioso - Câmara, Iara José Valente (2022)
With the reform of the Code of Civil Procedure (Law no. 41/2013, of June 26th), among other intentions, the legislator sought to eliminate procedural duplication in the context of precautionary procedures, introducing the regime of litigation’s inversion. This dissertation aims to analyze the problems of the regime of litigation’s inversion, predicted in article 369 and following of the Code of Civil Procedure. The regime of litigation’s inversion, as to its application, is materialized in the exemption of the applicant from the precautionary procedure of bringing the main action, in case the judge forms a secure conviction about the existence of the right and the order decreed is adequate to carry out the final composition of the dispute. Therefore, once the litigation’s reversion is settled, the defendant in the injunction now has to propose the main action. Thus, if the defendant does not file the main action, the injunction decreed definitively composes the litigation. A better explanation of the problems of the inversion of the litigation regime will require a general analysis of the cumulative requirements for the decree of the inversion of the litigation. The analysis of the procedural steps will be relevant for the study of the problems of the regime, given that the granting of the inversion of the litigation may raise issues of unconstitutionality, namely in cases where the defendant has not been previously heard. In this sense, it requires an individualized analysis of the circumstances that, if verified, impose the waiver of the defendant's prior hearing. Finally, the dissertation will focus on the doctrinal dispute about the distribution of the burden of proof in the main action brought by the defendant, with particular emphasis on the actions of simple negative appraisal, which will assume a primordial role in the study of the issues of the regime.